International recommendations for the assessment of autoantibodies to cellular antigens referred to as anti-nuclear antibodies. Issue 1 (14th October 2013) - Agmon-Levin, Nancy; Damoiseaux, Jan; Kallenberg, Cees; Sack, Ulrich; Witte, Torsten; Herold, Manfred; Bossuyt, Xavier; Musset, Lucille; Cervera, Ricard; Plaza-Lopez, Aresio; Dias, Carlos; Sousa, Maria José; et al.
Abstract : Anti-nuclear antibodies (ANA) are fundamental for the diagnosis of autoimmune diseases, and have been determined by indirect immunofluorescence assay (IIFA) for decades. As the demand for ANA testing increased, alternative techniques were developed challenging the classic IIFA. These alternative platforms differ in their antigen profiles, sensitivity and specificity, raising uncertainties regarding standardisation and interpretation of incongruent results. Therefore, an international group of experts has created recommendations for ANA testing by different methods. Two groups of experts participated in this initiative. The European autoimmunity standardization initiative representing 15 European countries and the International Union of Immunologic Societies/World Health Organization/Arthritis Foundation/Centers for Disease Control and Prevention autoantibody standardising committee. A three-step process followed by a Delphi exercise with closed voting was applied. Twenty-five recommendations for determining ANA (1–13), anti-double stranded DNA antibodies (14–18), specific antibodies (19–23) and validation of methods (24–25) were created. Significant differences between experts were observed regarding recommendations 24–25 (p<0.03). Here, we formulated recommendations for the assessment and interpretation of ANA and associated antibodies. Notably, the roles of IIFA as a reference method, and the importance of defining nuclear and cytoplasmic staining, were emphasised, while the need to incorporate alternative automated methods was acknowledged. Various approaches to overcome discrepancies between methods were suggested of which an improved bench-to-bedside communication is of the utmost importance. These recommendations are based on current knowledge and can enable harmonisation of local algorithms for testing and evaluation of ANA and related autoantibodies. Last but not least, new more appropriate terminologies have been suggested.